Peran Guru Dalam Mengembangkan Motorik Halus Anak - Asmawi Asmawi (Pena Islam Jurnal Pendidikan Agama Islam, 2022)
The teacher plays a role in teaching children, in this approach the teacher adheres to the guidelines of the abilities that the child will achieve by understanding the child's interests, feelings and experiences. This kind of approach is an effective and best approach because the child can develop as a whole. Data collection techniques use interviews, observations and documentation. Data analysis techniques use inductive analysis. Based on the results of the study, it can be seen that, The role of the teacher in developing fine motor skills is: a) The role of the teacher as a demonstrator, that is, the teacher has provided facilities to the child properly. b) The role of the Teacher as a Mediator in children at RA Mujahiddin, namely the teacher has given direction in learning to develop fine motor skills during learning activities. c) The Role of the Teacher as a Facilitator, the teacher gives an example in advance when the child wants to use learning media in doing fine motor activities, d) The role of the teacher in the implementation / management of learning in the classroom, namely by planning learning activities carefully. e) The Role of the Teacher as an Evaluator, it can be seen that the teacher observes the child in each activity using various learning media and the teacher gives an assessment after the child completes his task.